Lives of Substance: a mixed-method evaluation of a public information website on addiction experiences - Treloar, C.; Pienaar, Kiran; Dilkes-Frayne, E.; Fraser, Suzanne (Informa Healthcare, 2017)
The Lives of Substance (LoS) website presents personal experiences of drug use and ‘addiction’ in people’s own words as part of a larger project of complicating public discourses of addiction, countering stigmatising misconceptions and acting as an intervention in the social production of addiction. This article presents the findings of a mixed-method evaluation of the website, and comments on some of the methodological and practical challenges of evaluating health-related online information resources. Method: Three data sources were used to examine such as the reach of the website (website analytics); experiences of the website audience (responses to an evaluation survey on the website); and other indicators of use and impact (including social media referrals and organisational links). Results: In the 10-week evaluation period, 3970 unique users visited the website. Comments provided via the online survey endorsed the website as a means of challenging stereotypes and as presenting drug use as only a ‘part of a person’s whole life’. Twenty-four organisations had linked to the website and 987 social media referrals were recorded. Conclusion: These data indicate that the LoS website is having some success as a resource for countering addiction-related stigma and offering more holistic and inclusive social understandings of addiction.